2008
DOI: 10.1097/rli.0b013e31817e9ada
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging of the Ankle at 3.0 Tesla and 1.5 Tesla in Human Cadaver Specimens With Artificially Created Lesions of Cartilage and Ligaments

Abstract: Compared with 1.5-T imaging, the 3.0-T imaging of the ankle joint at improved diagnostic performance in assessing cartilage significantly and there was a higher sensitivity for assessing ligamentous pathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 42 publications
3
34
0
1
Order By: Relevance
“…However, in recent years, improvements of cartilage MR imaging were described. In particular, 3 T MRI is superior to 1.5 T MRI [8, 33, 34]. Improved visualization of the cartilage surface in high resolution MRI of the ankle was achieved by application of a traction device [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in recent years, improvements of cartilage MR imaging were described. In particular, 3 T MRI is superior to 1.5 T MRI [8, 33, 34]. Improved visualization of the cartilage surface in high resolution MRI of the ankle was achieved by application of a traction device [10].…”
Section: Discussionmentioning
confidence: 99%
“…With presence of metal implants, despite 1.5 T MR imaging and conventional and advanced metal artifact reducing sequences, MRI remains challenging [36]. In several studies, it has been shown that IM-w fs sequences perform best with respect to cartilage evaluation [8, 33]. However, spectral fat saturation is very sensitive to magnetic field inhomogeneities and does not work properly in case of presence of metal implants [37].…”
Section: Discussionmentioning
confidence: 99%
“…Barr et al reported, that compared to 1.5 T, 3.0 T significantly improved image quality and diagnostic performance in assessing ankle cartilage pathology [6]. IMfs or T2-w fs sequences have been reported to show the best diagnostic performance in the assessment of ankle cartilage [6,24]. On the contrary, Fischbach et al reported, that 3D GE fs sequences appear to be superior to T2-w fs FSE sequences [25].…”
Section: With Tractionmentioning
confidence: 92%
“…1). Meniscal anatomy acquired at 3.0 T has been demonstrated to be displayed with enhanced visibility while meniscal pathology obtained at 3.0 T has been shown to allow for better clinical assessment as demonstrated by the superior sensitivity and specificity measures when compared with lower field imaging systems (11, 13-16) (Fig. 2).…”
Section: Advantages Of Using 30 Tmentioning
confidence: 99%